2020
DOI: 10.1074/jbc.ra120.015592
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte nuclear factor 1β suppresses canonical Wnt signaling through transcriptional repression of lymphoid enhancer–binding factor 1

Abstract: Hepatocyte nuclear factor-1β (HNF-1β) is a tissue-specific transcription factor that is required for normal kidney development and renal epithelial differentiation. Mutations of HNF-1β produce congenital kidney abnormalities and inherited renal tubulopathies. Here, we show that ablation of HNF-1β in mIMCD3 renal epithelial cells results in activation of β-catenin and increased expression of lymphoid enhancer-binding factor 1 (LEF1), a downstream effector in the canonical Wnt signaling pathway. Increased expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…[15,30] Although a study showed that Wnt3α/β-catenin was involved in IN-17-induced proliferation, angiogenesis, and adhesion in HPAECs, [31,32] there were no other reports about the Wnt3α/β-catenin pathway in PASMCs. In this study, we found that Wnt3α/β-catenin promoted the proliferation LEF1 is the nuclear binding partner of β-catenin, [33][34][35][36][37] which bands with β-catenin and initiates the transcription of Wnt target genes. [38] LEF1 regulates cell growth and differentiation, while the abnormal expression of LEF1 is associated with tumorigenesis, cancer cell proliferation, migration, and invasion.…”
Section: Discussionmentioning
confidence: 81%
“…[15,30] Although a study showed that Wnt3α/β-catenin was involved in IN-17-induced proliferation, angiogenesis, and adhesion in HPAECs, [31,32] there were no other reports about the Wnt3α/β-catenin pathway in PASMCs. In this study, we found that Wnt3α/β-catenin promoted the proliferation LEF1 is the nuclear binding partner of β-catenin, [33][34][35][36][37] which bands with β-catenin and initiates the transcription of Wnt target genes. [38] LEF1 regulates cell growth and differentiation, while the abnormal expression of LEF1 is associated with tumorigenesis, cancer cell proliferation, migration, and invasion.…”
Section: Discussionmentioning
confidence: 81%
“…Accordingly, studies of mutant mice with kidney-specific deletion of HNF1B showed that early steps of renal MET are unaffected by HNF1B loss, with defects instead observed at comma-and S-shaped body stages, consistent with a role for HNF1B in the completion but not initiation of MET (Massa et al, 2013). HNF1B has also been reported to antagonise Wnt/b-Catenin signalling by both directly repressing LEF1 gene expression and by competitively binding and antagonising TCF/LEF1-target genes (Chan et al, 2020;Chan et al, 2019). Increased expression of HNF1B, for example by direct activation by PAX8 as we observed, could thus provide another possible feedback mechanism to limit Wnt/b-Catenin signalling during renal MET.…”
Section: Discussionmentioning
confidence: 95%
“…In fact, while the literature indicates potential HNF1b target genes and discusses its importance, there are only a few examples of validated HNF1b-enhancer interactions. It was reported to directly bind to regulatory elements in Lef1 and Axin2 gene loci in vitro ( 61 ), and several more targets were indicated in a Xenopus model (62). HNF1b itself is regulated by a Pax-8-responsive enhancer, and thus might be a promising target in a subsequent study (63).…”
Section: Discussionmentioning
confidence: 99%